2005
DOI: 10.1038/sj.cdd.4401736
|View full text |Cite
|
Sign up to set email alerts
|

Human 8-oxoguanine DNA glycosylase increases resistance to hyperoxic cytotoxicity in lung epithelial cells and involvement with altered MAPK activity

Abstract: It is unknown whether base excision DNA repair (BER) proteins interact with mitogen-activated protein kinases (MAPK) under oxidation. Here, we explored roles of BER proteins in signaling transduction involving MAPK during hyperoxia. We demonstrated that ERK1/2 phosphorylation in A549 cells was increased in 95% O 2 . p38 activity in A549 cells was also increased by exposure to 95% O 2 . To evaluate regulatory roles of MAPK, we have transduced A549 cells and primary alveolar epithelial type II cells (AECII) to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 54 publications
5
41
0
Order By: Relevance
“…For example, a decrease in hOGG1 confers cellular hypersensitivity to H 2 O 2 (30), and hOGG1-deficient human leukemia cells (KG-1) could be forced to undergo apoptosis by 8-hydroxyguanosine (31). On the other hand, the expression of hOGG1 suppresses the oxidative stress -derived DNA damages, followed by the enhanced cell survival (32)(33)(34). However, the exact mechanism by which oxidative stress -mediated DNA damage causes cell death is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a decrease in hOGG1 confers cellular hypersensitivity to H 2 O 2 (30), and hOGG1-deficient human leukemia cells (KG-1) could be forced to undergo apoptosis by 8-hydroxyguanosine (31). On the other hand, the expression of hOGG1 suppresses the oxidative stress -derived DNA damages, followed by the enhanced cell survival (32)(33)(34). However, the exact mechanism by which oxidative stress -mediated DNA damage causes cell death is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hyun et al (2000) demonstrated that OGG1-deficient human leukemia cells might be required to undergo apoptosis by 8-OhdG. Conversely, expression of OGG1 suppressed oxidative stress derived DNA damage and enhanced cell survival (Kannan et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated with primary Abs at a 1:500 dilution in blocking buffer for 1 h and washed three times with wash buffer. After incubation with appropriate fluorophore-conjugated secondary Abs, the coverslips were mounted on slides with VECTASHIELD mounting medium (36). DAPI (SigmaAldrich) was used to stain the nucleus.…”
Section: Confocal Microscopy and Indirect Immunofluorescencementioning
confidence: 99%